192k views
5 votes
Fill in the table using this function rule.y=3x-1хy1 3O069

User Saketrp
by
5.3k points

1 Answer

7 votes

Answer:

x y

1 2

3 8

6 17

9 26

Step-by-step explanation:

The table of values we have to fill is:

x y

1

3

6

9

And the function we have is:


y=3x-1

To fill the table, we need to take each value of x, and substitute it on the function to find y.

Starting with x = 1


\begin{gathered} y=3(1)-1 \\ y=3-1 \\ y=2 \end{gathered}

So we update the table

x y

1 2

3

6

9

Next, we substitute the value x = 3 into the function


\begin{gathered} y=3(3)-1 \\ y=9-1 \\ y=8 \end{gathered}

x y

1 2

3 8

6

9

Now the value of x =6


\begin{gathered} y=3(6)-1 \\ y=18-1 \\ y=17 \end{gathered}

x y

1 2

3 8

6 17

9

Finally we substitute x =9 into the function


\begin{gathered} y=3(9)-1 \\ y=27-1 \\ y=26 \end{gathered}

And the table is:

x y

1 2

3 8

6 17

9 26

User Pdinklag
by
5.4k points